Retail strategy : planning and control - Walsh, Sue.; Hanrahan, Jack. (Basingstoke : Macmillan, 2000)
This book presents the Environment of Retail Strategy, Background to Strategy, Operational management and Strategy, Performance evaluation...
Keywords: Management; Retail trade; Retail trade -- Management